Enriching value chains through maps: reflections from spatial group model building in Myanmar and India. Issue 2 (17th February 2022) - Rich, Karl M.; Berends, Jared; Cooper, Gregory S.
ABSTRACT: Recent research has highlighted the valuable contributions that participatory processes contribute in developing system dynamics models of value chains with stakeholders. A new participatory process known as spatial group model building (SGMB) expands these insights, using maps and GIS concepts to improve the facilitation and modelling process. This practical note provides an overview of SGMB, its recent applications in informing development interventions, and proposed innovations to expand its use and dissemination.